Uparqual: The Development Of An Urban Park Satisfaction Measurement Scale - Norizan, Jaafar; Rabaah, Tudin (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The tourism industry is experiencing rapid growth and Malaysia is, in turn, encouraging domestic tourists. Hence, providing quality leisure experiences to tourists is important, since it will lead to increased frequency of visits, as well as increased fulfilment from these visits. A quality leisure experience can be acquired by visiting many spots in a given destination, including urban parks. Urban parks can easily be found in almost every city in Malaysia as an avenue for outdoor recreational activities, socialising and relaxation. An urban park is designed specifically for local tourists from the urban population. Increasing the number of tourists to urban parks whilst retaining their interest should result in leisure experiences meeting the satisfaction of tourists. The purpose of this study is to develop a multi-dimensional measurement scale of service quality for tourist satisfaction in urban parks. The present study was conducted at an urban park located in Kuching, Sarawak. Primary data was collected using a non-probability convenience sampling technique, with 300 of the 400 distributed questionnaires returned and usable. Based on the findings of this study, a proposed new instrument, “UPARQUAL” was developed to gauge tourist satisfaction at urban parks. UPARQUAL, a six-dimensional instrument, was empirically tested and deemed appropriate for measuring the level of satisfaction that tourists experience in these urban parks. In addition, this study also recommends several measures to increase of tourist satisfaction.